The World and its wonders - Blackwood, Paul Everett, 1913- (Chicago, Ill. : Child's World, 1971)
Includes brief articles in the areas of astronomy, geology, meteorology, energy, commerce and industry, and space exploration.
Keywords: Science -- Juvenile literature; Science